The SPATIAL DISTRIBUTION PATTERNS OF BENTHIC MACROALGAE ALONG UJUNG GENTENG COAST, SUKABUMI, WEST JAVA - Raden Indarjani; Muhamad Rizky; Miftahul Jannah (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- The study in Ujung Genteng coast presents clear evidence of moderate macroalgae diversities and community structure linked to environmental parameters and substrate type- The biological indices scores illustrated a spatial distribution pattern of macroalgae assemblages- Understanding these ecological dynamics of macroalgae is crucial for both conservation and sustainable seaweed cultivation.ABSTRACTThe study of benthic macroalgae in Ujung Genteng aimed to describe the spatial distribution pattern of benthic macroalgae based on various parameters that support their growth and influence the health status of the marine ecosystem. The study was conducted from May to December 2023. The observation sites were selected using a purposive sampling method across three coastal areas, chosen based on the physical landscape structure and distinct substrate types. The line transect quadrat method was used for data collection. The study identified 41 species of benthic macroalgae from 28 genera and 19 families. The bubble green algae Boergesenia forbesii emerged as the dominant species, accounting for 16.8% of the assemblages, although this difference was not statistically significant. The distribution pattern of macroalgae showed noticeable spatial variation, with the East Zone, located in the eastern part of the coastal area, considered the most favourable habitat, harbouring 32 species with 312 individuals. The health status of the marine ecosystem in Ujung Genteng was relatively good, indicated by moderate Diversity Index (H’) values around 2.52 to 2.70, high Evenness Index (E) values (0.73 to 0.82), and low Dominance Index (D) values (0.09 to 0.11). The measured abiotic factors also fell within ranges that support the growth of benthic macroalgae. Keywords: benthic macroalgae, spatial, distribution patterns, Ujung Genteng